Identification of proteins associated with development of metastasis from cutaneous squamous cell carcinomas (cSCCs) via proteomic analysis of primary cSCCs. (1st April 2021) - Shapanis, A.; Lai, C.; Smith, S.; Coltart, G.; Sommerlad, M.; Schofield, J.; Parkinson, E.; Skipp, P.; Healy, E.
Summary: Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most common cancers capable of metastasizing. Proteomic analysis of cSCCs can provide insight into the biological processes responsible for metastasis, as well as future therapeutic targets and prognostic biomarkers. Objectives: To identify proteins associated with development of metastasis in cSCC. Methods: A proteomic‐based approach was employed on 105 completely excised, primary cSCCs, comprising 52 that had metastasized (P‐M) and 53 that had not metastasized at 5 years post‐surgery (P‐NM). Formalin‐fixed, paraffin‐embedded cSCCs were microdissected and subjected to proteomic profiling after one‐dimensional (1D), and separately two‐dimensional (2D), liquid chromatography fractionation. Results: A discovery set of 24 P‐Ms and 24 P‐NMs showed 144 significantly differentially expressed proteins, including 33 proteins identified via both 1D and 2D separation, between P‐Ms and P‐NMs. Several differentially expressed proteins were also associated with survival in SCCs of other organs. The findings were verified by multiple reaction monitoring on six peptides from two proteins, annexin A5 (ANXA5) and dolichyl‐diphosphooligosaccharide–protein glycosyltransferase noncatalytic subunit (DDOST), in the discovery group and validated on a separate cohort ( n = 57). Increased expression of ANXA5 and DDOST was associated with reduced time to metastasis in cSCC and decreased survival in cervical and oropharyngeal cancer. A prediction model using ANXA5 and DDOST had an area under the curve of 0·93 (confidence interval 0·83–1·00), an accuracy of 91·2% and higher sensitivity and specificity than cSCC staging systems currently in clinical use. Conclusions: This study highlights that increased expression of two proteins, ANXA5 and DDOST, is significantly associated with poorer clinical outcomes in cSCC.